The Effectiveness of the Working Area of the Land Deed Making Officer Based on Government Regulation Number 24 of 2016 in One Bali Province - Yasaputri, Ni Putu Widari; Wesna, Putu Ayu Sriasih; Utama, I Wayan Kartika Jaya (Journal of Legal and Cultural Analytics, 2025)
This study examines the effectiveness of Government Regulation Number 24 of 2016 which expands the work area of PPAT from districts/cities to one province. The method uses empirical legal research by elaborating the theory of legal certainty, legal effectiveness, and legal authority. Data was obtained through observation and interviews in Badung and Bangli Regencies. The results show that the implementation has not been effective due to the absence of implementing regulations, thus causing legal uncertainty and potential conflicts of authority. This study recommends accelerating the preparation of technical regulations to support the effectiveness of land administration.